Użytkownicy i zasób repozytorium instytucjonalnego (studium przypadku) - Rychlik, Małgorzata; Theus, Monika (My University, 2016)
Teza/cel artykułu – Jednym z dwóch głównych celów artykułu jest przeanalizowanie zasobu największego w Polsce repozytorium instytucjonalnego AMUR pod kątem typów obiektów archiwizowanych na platformie oraz ich zakresu tematycznego. Drugim celem jest pozyskanie danych na temat użytkowników repozytorium AMUR. Metody – Pierwszy etap badania polegał na pobraniu statystyk użytkowania zasobu repozytorium, a drugi na pobraniu danych dotyczących użytkowników z serwisu Google Analytics. Wyniki/wnioski – W wyniku przeprowadzonego badania określono, iż najczęściej pobieranymi typami obiektów były prace doktorskie oraz materiały dydaktyczne. Wykazano, że istnieje wyraźna tendencja wskazująca na większą popularność prac z dziedzin reprezentujących nauki humanistyczne i społeczne. Użytkownicy repozytorium najczęściej trafiali do zasobu poprzez wyszukiwarkę Google (60%). Ponad 11% użytkowników rozpoczynało wyszukiwanie bezpośrednio ze strony platformy AMUR a około 30% z nich powracało do zasobu repozytorium.

Objective – The present paper focuses on a number of major aspects of institutional repository data collecting, such as the type of objects to be archived and their thematic scope. The authors examine the resources of the AMUR repository, currently the biggest institutional repository platform in Poland. Yet another objective of the present investigation is to provide reliable data on the users of the AMUR repository. Methods – The first stage of the investigation was to collect usage statistics relative to the content of repository holdings and user activity, whereas the second stage involved data mining of data on users using Google Analytics. Results/conclusions – As a result of the study it was determined that the most frequently downloaded types of objects were doctoral dissertations and learning resources. It has been proved that there is a clear tendency in that works representing the humanities and social sciences are decidedly more in demand than any other available material. Different users accessed the website of the repository primarily through the Google searching engine (60%). Over 11% of the users started their searchers directly from the web page of the AMUR platform, while about 30% of them returned to the resources of the repository.
Users and content of an institutional repository (case study)
Keywords: repozytorium instytucjonalne; repozytorium AMUR; użytkownik repozytorium; zasób repozytorium; institutional repository; AMUR repository; institutional repository end user; repository content